Síntomas asociados al tratamiento con radioterapia - Murillo, María Teresa; Valentín, Vicente; Valentín, María (Psicooncología, 2004)
The principles of radiotherapy are the use of ionized radiation in the treatment of different pathologic process. The objective of radiotherapy treatment is the local or locorregional control of the tumor. The onset of side effects depends of the dose of radiation and the area that is included in the treatment field. The acute affects usually appear at the beginning of the treatment and usually disappear at the end or in the first weeks after the end of the treatment. The chronic effects appear 6 months after the treatment is finished and they persist during time. The most frequents side effects are fatigue and changes in the skin included in the treatment field. The other side effects are in relationship of the specific area that we are treating. With the improvements in the radiotherapy treatments we can achieve a better local tumor control with lesser chronic side effects.